Penyuluhan Kesehatan Untuk Meningkatkan Pemahaman Tentang Menjaga Kebersihan Telinga - Zhalif Zhafir Aghna; Imanto, Mukhlis (CV. Jasa Sukses Abadi, 2024)
The habit of cleaning the external auditory canal (EAC) with cotton buds and other objects is a common practice. Among the general public, ears are believed to need to be cleaned frequently to remove dirt in the form of earwax. This is usually done by inserting objects into the ear itself, most often with Q-tips also known as cotton buds. Medical concerns over cotton bud use and its complications were first reported in 1972, with reports of tympanic membrane perforation, otitis externa, and cerumen impaction. Today, cotton bud-related injuries have become a common reason for visits to ear, nose, and throat clinics. The purpose of this activity is to increase public understanding of how to properly maintain ear hygiene and reduce the incidence of complications due to lack of understanding about it. The target of this activity is 20 patients at the Abdul Moeloek Hospital Polyclinic, Lampung Province on November 21, 2023, 10:00-12:00 WIB. The form of this activity includes providing material on maintaining ear hygiene properly followed by discussion. The results of this activity are that there are still some patients who still have a low level of understanding, attitude, and practice regarding maintaining ear hygiene and health. After counseling, there was an increase in understanding, attitudes, and practices among respondents which is expected to increase knowledge among individual, family, and community components in maintaining ear hygiene.